KOMIK SEBAGAI MEDIA PENGAJARAN BAHASA YANG KOMUNIKATIF BAGI SISWA SMP - Johana, Maria; Widayanti, Ari (Universitas Negeri Semarang, 2007)
English has been learned since elementary school up to some semesters atuniversities. As a foreign and second language, communicative language teaching(CLT) could be done. The problem is: How comic can be used to teach readingcommunicatively at Junior High School? There are four teaching skills at Junior HighSchool’s level: reading, listening, speaking, and writing. Reading is one of four skillsthat is very important to be mastered by students. As a kind of reading text, comics arebrief and easy to understand. Comics as the teaching media can be used to motivatestudents enjoy in reading. At the communicative language teaching, the role of teacheris as a facilitator and allowing students involves in this learning process. Although ateacher is a facilitator, teacher still gives some assignments and instructions at class. Ateacher motivates students in speaking to reveal their thoughts. Students canparticipate actively in the language teaching process.Kata kunci: pembalajaran bahasa komunikatif, komik, media, definisi membaca